Muscles of the trunk and pelvis are responsive to testosterone administration: data from testosterone dose–response study in young healthy men. (26th December 2017) - Tapper, J.; Arver, S.; Pencina, K. M.; Martling, A.; Blomqvist, L.; Buchli, C.; Li, Z.; Gagliano‐Jucá, T.; Travison, T. G.; Huang, G.; Storer, T. W.; Bhasin, S.; et al.
Abstract: Testosterone dose‐dependently increases appendicular muscle mass. However, the effects of testosterone administration on the core muscles of the trunk and the pelvis have not been evaluated. The present study evaluated the effects of testosterone administration on truncal and pelvic muscles in a dose–response trial. Participants were young healthy men aged 18–50 years participating in the 5α‐Reductase (5aR) Trial. All participants received monthly injections of 7.5 mg leuprolide acetate to suppress endogenous testosterone production and weekly injections of 50, 125, 300, or 600 mg of testosterone enanthate and were randomized to receive either 2.5 mg dutasteride (5aR inhibitor) or placebo daily for 20 weeks. Muscles of the trunk and the pelvis were measured at baseline and the end of treatment using 1.5‐Tesla magnetic resonance imaging. The dose effect of testosterone on changes in the psoas major muscle area was the primary outcome; secondary outcomes included changes in paraspinal, abdominal, pelvic floor, ischiocavernosus, and obturator internus muscles. The association between changes in testosterone levels and muscle area was also assessed. Testosterone dose‐dependently increased areas of all truncal and pelvic muscles. The estimated change (95% confidence interval) of muscle area increase per 100 mg of testosterone enanthate dosage increase was 0.622 cm 2 (0.394, 0.850) for psoas; 1.789 cm 2 (1.317, 2.261) for paraspinal muscles, 2.530 cm 2 (1.627, 3.434) for total abdominal muscles, 0.455 cm 2 (0.233, 0.678) for obturator internus, and 0.082 cm 2 (0.003, 0.045) for ischiocavernosus; the increase in these volumes was significantly associated with the changes in on‐treatment total and free serum testosterone concentrations. In conclusion, core muscles of the trunk and pelvis are responsive to testosterone administration. Future trials should evaluate the potential role of testosterone administration in frail men who are predisposed to falls and men with pelvic floor dysfunction.